1992
DOI: 10.2307/2410032
|View full text |Cite
|
Sign up to set email alerts
|

Algae Containing Chlorophylls a + c are Paraphyletic: Molecular Evolutionary Analysis of the Chromophyta

Abstract: Sequence comparisons of small subunit ribosomal RNA coding regions from 12 chlorophylls a + c-containing algae were used to infer phylogenetic relationships within the Chromophytao Three chromophyte lines of descent, delineated by the Bacillariophyceae, the Phaeophyceael Xanthophyceae, and the Chrysophyceae/Eustigmatophyceae/Synurophyceae are members of a complex evolutionary assemblage, which also includes representatives of the Oomycota ("lower" fungi). Maximum parsimony and distance matrix methods demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
54
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 16 publications
7
54
1
Order By: Relevance
“…The fact that complete rRNA sequences later supported their monophyly does not alter the fact that the morphological evidence against the premature conclusion was unwisely discounted. Other cases where morphology pointed to monophyly, but was more controversial, but where it was claimed to have been disproved by rRNA are the phylum Mycetozoa (apparently contradicted by numerous trees) and the kingdoms Plantae (contradicted by Bhattacharya et al, 1990) and Chromista (contradicted by Bhattacharya et al, 1991 ;Bhattacharya & Medlin, 1995 ;Oliveira & Bhattacharya, 2000).…”
Section: Bacterial Megaclassificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that complete rRNA sequences later supported their monophyly does not alter the fact that the morphological evidence against the premature conclusion was unwisely discounted. Other cases where morphology pointed to monophyly, but was more controversial, but where it was claimed to have been disproved by rRNA are the phylum Mycetozoa (apparently contradicted by numerous trees) and the kingdoms Plantae (contradicted by Bhattacharya et al, 1990) and Chromista (contradicted by Bhattacharya et al, 1991 ;Bhattacharya & Medlin, 1995 ;Oliveira & Bhattacharya, 2000).…”
Section: Bacterial Megaclassificationmentioning
confidence: 99%
“…The fact that complete rRNA sequences later supported their monophyly does not alter the fact that the morphological evidence against the premature conclusion was unwisely discounted. Other cases where morphology pointed to monophyly, but was more controversial, but where it was claimed to have been disproved by rRNA are the phylum Mycetozoa (apparently contradicted by numerous trees) and the kingdoms Plantae (contradicted by Bhattacharya et al, 1990) and Chromista (contradicted by Bhattacharya et al, 1991 ;Bhattacharya & Medlin, 1995 ;Oliveira & Bhattacharya, 2000).Protein trees have clearly established the monophyly of Mycetozoa (Baldauf & Doolittle, 1997 ;Baldauf et al, 2000) and Plantae sensu Cavalier-Smith 1981(Moreira et al, 2000Baldauf et al, 2000). The recent evidence from the duplication and retargeting of glyceraldehyde-phosphate dehydrogenase (Fast et al, 2001) decisively shows chromalveolates (Chromista plus alveolates ; Cavalier-Smith, 1999, 2000a to be monophyletic (McFadden, 2000), making it highly probable that Chromista are also.…”
mentioning
confidence: 99%
“…In addition to diatom sequences presented in Bhattacharya et al (1992), we have included sequence data for five more diatom species (Tabl e 2), which have been deposited in Genbank. The sequences were aligned using two methods.…”
Section: Molecular Character Analysismentioning
confidence: 99%
“…Recently, Bhattacharya et al (1992) have shown, using small subunit (ssu) rRNA sequence data, that the diatoms are correctly placed in a chromophyte/ oomycete lineage that excludes dinoflagellates and prymnesiophytes. We have employed this same technique to assess the relationships among diatoms and the relationship of the diatoms to other groups within the chromophyte/oomycete lineage.…”
Section: Introductionmentioning
confidence: 99%
“…The haptophytes and stramenopiles share characteristics such as tubular mitochondrial cristae, similar storage products, and fucoxanthin that suggest a specific relationship between these taxa (9). Stramenopiles include autotrophic and heterotrophic species that may differ enormously in their morphology and mode of life.…”
mentioning
confidence: 99%